Existence Theorems for Quasivariational Inequality Problem on Proximally Smooth Sets - Jittiporn Suwannawit; Narin Petrot (Abstract and Applied Analysis)
The concept of quasivariational inequality problem on proximally smooth sets is studied. Some sufficient conditions for solving the existence of solutions of such a problem are provided; also some interesting cases are discussed. Of course, due to the significance of proximally smooth sets, the results which are presented in this paper improve and extend many important results in the literature.